2007
DOI: 10.1007/s10646-007-0160-2
|View full text |Cite
|
Sign up to set email alerts
|

Temporal trends of mercury concentrations in Wisconsin walleye (Sander vitreus), 1982–2005

Abstract: The Wisconsin Department of Natural Resources has monitored mercury (Hg) in several species of fish since the early 1970s primarily for fish consumption advisory purposes. We selected skin-on fillets of walleye (Sander vitreus) from inland lakes collected over the years 1982-2005 to assess temporal trends of Hg concentrations. While individual lakes are of interest, sample sizes, and unbalanced collections across fish lengths, seasons, or years prevent estimates of temporal trends of walleye Hg concentrations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
46
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 45 publications
(49 citation statements)
references
References 43 publications
3
46
0
Order By: Relevance
“…Other previous statistical models of fish-Hg trends have not included the categorical variable of waterbody type. Previous studies have limited the Hg trend analysis to only lakes, excluding the river and impoundment data, because lakes are more likely to show a relationship to atmospheric deposition of Hg (e.g., Madsen and Stern 2007;Rasmussen et al 2007;Monson 2009). …”
Section: Output Summarymentioning
confidence: 99%
See 1 more Smart Citation
“…Other previous statistical models of fish-Hg trends have not included the categorical variable of waterbody type. Previous studies have limited the Hg trend analysis to only lakes, excluding the river and impoundment data, because lakes are more likely to show a relationship to atmospheric deposition of Hg (e.g., Madsen and Stern 2007;Rasmussen et al 2007;Monson 2009). …”
Section: Output Summarymentioning
confidence: 99%
“…Trend analysis of walleye (Sander vitreus) in Wisconsin lakes between 1982 and 2005 has shown an annual percent change (APC) of 0.5 to 0.6% in northern Wisconsin and an upward trend of 0.8% APC in southern Wisconsin (Madsen and Stern 2007;Rasmussen et al 2007). Over the same period in Minnesota (1982Minnesota ( -2006, the overall trend in walleye and northern pike (Esox lucius) was the same as northern Wisconsin, but a better fitting piecewise linear regression model indicated a steeper decline of 4.7% per year from 1982 to 1992, followed by an increase of 1.4% per year for 1992-2006 (Monson 2009).…”
Section: Introductionmentioning
confidence: 99%
“…For example, within-lake concentrations of mercury in these piscivorous fish decreased in 35% but increased in 60% of lakes. Concentrations of mercury in walleye in northern Wisconsin have also decreased by about 0.5% annually between 1982 and 2005, remained relative constant in the middle latitude lakes of the state, but have increased approximately 0.8% annually in southern Wisconsin (Madsen and Stern 2007;Rasmussen et al 2007). Bhavsar et al (2010) reported that, since 1990, mercury in walleye has declined in Lake Superior (0.18-0.20 lg g -1 wet weight per decade) and Lake Huron (0.05-0.07 lg g -1 wet weight per decade), remained unchanged in Lake Ontario, and has increased in Lake Erie (0.036 lg g -1 wet weight per decade).…”
Section: Estimated Mercury Concentration In Standard-size Fishmentioning
confidence: 99%
“…Indeed, pH remained stable in most lakes, and increased in relatively few lakes, in Ontario, Quebec, Nova Scotia, and Newfoundland during the 1990s, perhaps requiring decades before pH increases in most lakes (e.g., Kemp 1999, Clair et al 2002, Jefferies et al 2003a. Similarly, methylmercury concentrations increased in fish and loons in widely scattered eastern locations between the mid-1990s and mid-2000s (Madsen and Stern 2007, Monson 2009, Rasmussen et al 2007, Wyn et al 2010.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, methylmercury concentrations are increasing in some locations because of multiple interacting factors that cause methylmercury to increase even though mercury deposition and acid precipitation have declined (Watras and Morrison 2008). For example, methylmercury increased in fish between the mid-1990s and mid-2000s in Wisconsin, Minnesota, and Nova Scotia (Madsen and Stern 2007, Monson 2009, Rasmussen et al 2007, Wyn et al 2010 and mercury increased in Common Loons from 2002 to 2010 in Wisconsin (Meyer et al 2011). Similarly, pH increased in relatively few lakes in eastern Canada during the 1990s, despite concurrent reductions in acid emissions, partly because the acid neutralizing capacity of most lakes remained insufficient to buffer acid inputs (Doka et al 2003, Jefferies et al 2003a.…”
Section: Introductionmentioning
confidence: 99%